2012
DOI: 10.1021/ct300509d
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Molecular Orbital Model Chemistry 3. The PMO Method Extended to Organic Chemistry

Abstract: The polarized molecular orbital (PMO) method, a neglect-of-diatomic-differential-overlap (NDDO) semiempirical molecular orbital method previously parameterized for systems composed of O and H, is here extended to carbon. We modified the formalism and optimized all the parameters in the PMO Hamiltonian by using a genetic algorithm and a database containing both electrostatic and energetic properties; the new parameter set is called PMO2. The quality of the resulting predictions is compared to results obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…58,59 Three key modifications were introduced in PMO. Since the method has been reported in detail previously, 35,[51][52][53] we only provide a brief summary of its key departures from MNDO.…”
Section: A Polarized Molecular Orbital Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…58,59 Three key modifications were introduced in PMO. Since the method has been reported in detail previously, 35,[51][52][53] we only provide a brief summary of its key departures from MNDO.…”
Section: A Polarized Molecular Orbital Methodsmentioning
confidence: 99%
“…At present, three different variations of the PMO method have been reported, PMOv1, 52 PMO2, 53 and PMOw, 35 none of which contain parameters for fluorine. The variant of PMO for which we have decided to introduce the F parameters is the PMOw model, having kept all other parameters fixed to those reported in Ref.…”
Section: A Polarized Molecular Orbital Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47][48][49] Another important deficiency of many semiempirical models for treating nonbonded interactions is that molecular polarization is systematically underestimated. Recently, we have introduced a polarized molecular orbital (PMO) alternative, [49][50][51] in which a set of p-orbitals are added to each hydrogen atom. 52 It was found that the computed molecular polarizabilities for a range of compounds containing hydrogen, carbon, and oxygen are significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…52 It was found that the computed molecular polarizabilities for a range of compounds containing hydrogen, carbon, and oxygen are significantly improved. 49,51 Employing this strategy, we report here a parametrization of the PMO model for water (PMOw), which can be used in X-Pol for liquid simulations.…”
Section: Introductionmentioning
confidence: 99%